THE WORD FORMATION PROCESSES OF INDONESIAN SLANG WORDS USED IN COSMO GIRL! INDONESIAN TEENAGE MAGAZINE - Victor S. Kusuma; J. J. Mardijono (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This was a qualitative study of word formation processes of Indonesian slang words in the Cosmo Girl!. To reveal the type of word formation and the most frequent type of word formation processes, the writer used two theories of word formation processes, namely word formation processes by Yule (2006) supported by Indonesian word formation processes by Chaedar (1994). The findings revealed four types of word formation processes, namely Clipping (3.22%), Blending (3.22%), Borrowing (19.35%) and Multiple Processes (74.19%). Although the Multiple Processes took a crucial part in forming Indonesian slang words, the process of borrowing dominantly occurred in the Multiple Processes. Especially English was often used in the borrowing process. Besides, the findings revealed processes that are not stated in both of the theories, namely Addition, Substitution and Deletion. These three processes were needed to adjust to Indonesian spelling system.